Kinerja Pemerintah Desa Dalam Pengelolaan Anggaran Dana Desa Di Desa Gorontalo Kabupaten Manggarai Barat - Bertholdus Olencky Onta; Cataryn V. Adam; Rouwland A. Benyamin; Nursalam (PT. Hasba Edukasi Mandiri, 2025)
The performanceof the Village Head is the level of success of the village head in carrying out his duties andfunctions as the head of the village government, which in the management of the village budget the village head must be able to maximize the existing budget and utilize the existing human resources in the village to support village development. In this case, the performance of the village head is measured using the theory of performance indicators put forward by Prof. DR. Prasojo Eko. Which discusses related to Transparency, Accountability, Community Engagement, Effectiveness, Efficiency, and Regulatory Compliance. This research uses a qualitative approach by using a qualitative descriptive method with data collection techniques such as observation, interviews, and documentation.The results of the study show that the performance of the village head is still less effective which is where the lack of information disclosure to the community so that many people do not know about the management of the village fund budget, the responsibility of the village government related to the management of the village budget is also not satisfactory for the community, low community participation also affects the process of managing the village fund budget, the lack of equitable distribution of development in every Gorontalo village area, Lack of utilization of existing human resources and lack of time utilization so that it causes significant financing, the village government in managing the village fund budget is in accordance with the existing rules in the management of the village fund budget.